ASOSIASI PENGETAHUAN, PELATIHAN DAN STIMULAN TERHADAP KINERJA KADER POSYANDU BALITA: STUDI DI SURAKARTA, JAWA TENGAH INDONESIA - Noor Alis Setiyadi setiyadi; Like Anggita Destiana Putri (LLDIKTI Wilayah X, 2023)
Health volunteers are important figures in the implementation of Posyandu, i.e integrated service corner. If the they are not active, the implementation of the Posyandu will not run smoothly so that the nutritional status of toddlers cannot be detected early and clearly. Therefore, in implementing of posyandu, health volunteers must have high performance. This study aimed to determine the relationship between knowledge, training, incentives and the performance of health volunteers. This type of research was quantitative research with a community-based cross-sectional approach. This research was conducted in the Manahan Community Health Centre with 125 respondents. The technique sampling was simple random sampling and data analysis used was chi-square test. The results showed that there were no relationship between knowledge of p-value 0.416, OR= 0.739 (95% CI: 0.356-1.534), training p-value 0.884, OR= 1.055 (95% CI: 0.515-2.160) and incentives p-value 0.162, OR= 1.714 (95% CI: 0.804-3.657) and the performance of Posyandu health volunteer. Although there were the significant relationship between knowledge, training, and incentives, but the incentives factor had a probability of 1.7 times to be high performance of posyandu health volunteer. For this reason, the government or policy makers are expected to pay attention to incentives to improve the performance of posyandu health volunteers